PERANAN WALI HAKIM DALAM PERKAWINAN : (Studi Kasus di KUA Kecamatan Suli Kabupaten Luwu) - Ismayanti Rais; Muh. Saleh Ridwan; Andi Intan Cahyani (Qadauna: Jurnal Ilmiah Mahasiswa Hukum Keluarga Islam, 2022)
The main problem in the research is how the role of guardian judges in marriage, case study at KUA Suli District Luwu Regency. The type of research used in this is field research. The results of this study indicate that the role of guardian judges in marriage at the Office of Religious Affairs (KUA) Suli District, Luwu Regency, namely marrying prospective brides who do not have a guardian or guardian adhal (reluctant/refused) then the guardianship is transferred to the guardian judge in this case the head of the KUA , as in the Regulation of the Minister of Religion Number 30 of 2005 concerning Guardian Judges. Then, before the head of the KUA acts as the guardian of the judge, it is necessary to do research first by the KUA that shows the truth of the guardianship issue of the prospective bride. With the existence of a marriage guardian in marriage, it can play a role in protecting women from the possibility of harm in their marital household, as well as the fulfillment of the conditions and pillars of marriage in advance. Keywords: Guardian Judge, Marriage.